Global variations in the prevalence, treatment, and impact of atrial fibrillation in a multi-national cohort of 153 152 middle-aged individuals - Joseph, Philip G; Healey, Jeffrey S; Raina, Parminder; Connolly, Stuart J; Ibrahim, Quazi; Gupta, Rajeev; Avezum, Alvaro; Dans, Antonio L; Lopez-Jaramillo, Patricio; Yeates, Karen; Teo, Koon; Douma, Reuben; et al. (Cardiovascular research, 2021)
To compare the prevalence of electrocardiogram (ECG)-documented atrial fibrillation (or flutter) (AF) across eight regions of the world, and to examine antithrombotic use and clinical outcomes. Baseline ECGs were collected in 153 152 middle-aged participants (ages 35-70 years) to document AF in two community-based studies, spanning 20 countries. Medication use and clinical outcome data (mean follow-up of 7.4 years) were available in one cohort. Cross-sectional analyses were performed to document the prevalence of AF and medication use, and associations between AF and clinical events were examined prospectively. Mean age of participants was 52.1 years, and 57.7% were female. Age and sex-standardized prevalence of AF varied 12-fold between regions; with the highest in North America, Europe, China, and Southeast Asia (270-360 cases per 100 000 persons); and lowest in the Middle East, Africa, and South Asia (30-60 cases per 100 000 persons) (P < 0.001). Compared with low-income countries (LICs), AF prevalence was 7-fold higher in middle-income countries (MICs) and 11-fold higher in high-income countries (HICs) (P < 0.001). Differences in AF prevalence remained significant after adjusting for traditional AF risk factors. In LICs/MICs, 24% of participants with AF and a CHADS2 score ≥1 received antithrombotic therapy, compared with 85% in HICs. AF was associated with an increased risk of stroke [hazard ratio (HR) 2.29; 95% confidence interval (CI) 1.49-3.52] and death (HR 2.97; 95% CI 2.25-3.93); with similar rates in different countries grouped by income level. Large variations in AF prevalence occur in different regions and countries grouped by income level, but this is only partially explained by traditional AF risk factors. Antithrombotic therapy is infrequently used in poorer countries despite the high risk of stroke associated with AF.